Role of Huangqin Qingre Chubi Capsule in the Reduction of the Risk of Re-Admission in Patients With Ankylosing Spondylitis: A Cohort Study - Qi Y; Liu J; Chen Y; Hu Y; Zhou Q; Huang D; Cong C; Li Y (International Journal of General Medicine, 2025)
Yajun Qi,1– 3 Jian Liu,1,3 Yiming Chen,1,3 Yuedi Hu,1,3 Qiao Zhou,1,3 Dan Huang,1,3 Chengzhi Cong,1,3 Yang Li1,3 1The First College of Clinical Medicine, Anhui University of Chinese Medicine, Hefei, Anhui Province, 230031, People’s Republic of China; 2College of Acupuncture and Massage, Anhui University of Chinese Medicine, Hefei, Anhui Province, 230012, People’s Republic of China; 3Department of Rheumatology and Immunology, The First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui Province, 230031, People’s Republic of ChinaCorrespondence: Jian Liu, Department of Rheumatology and Immunology, The First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui Province, 230031, People’s Republic of China, Email liujianahzy@126.comObjective: This study evaluates whether Huangqin Qingre Chubi Capsule (HQC), a traditional Chinese medicine (TCM) compound, is associated with the risk of re-admission in patients with ankylosing spondylitis (AS).Methods: In this study, we retrospectively collected the clinical data of 1,296 AS patients. Patients were allocated into HQC and non-HQC groups. Baseline data between the two groups were matched with propensity score matching (PSM). Influencing factors for the risk of re-admission in AS patients were analyzed with the Cox proportional hazards model. The effect of HQC intervention duration on the risk of re-admission was assessed with Kaplan-Meier survival curves. The random walk model and association rule analysis were utilized to determine the correlation between HQC and improvements in immunoinflammatory markers.Results: The re-admission rate was significantly lower in the HQC group than in the non-HQC group (P < 0.01). The risk of re-admission was significantly lower in patients aged > 40 years (P < 0.01) than in patients aged < 40 years and also markedly lower in HQC users than in non-HQC users (P < 0.01), suggesting that age and the use of HQC were key factors influencing the risk of re-admission. Longer HQC intervention duration was associated with better improvements in ESR, CRP, and C4, and HQC was closely correlated with improvements in ESR, CRP, IgA, and C4.Conclusion: HQC treatment can reduce the risk of re-admission in AS patients, which may be associated with improvements in ESR, CRP, IgA, and C4. The risk decreases with prolonged HQC treatment.Keywords: Huangqin Qingre Chubi Capsule, ankylosing spondylitis, re-admission, cohort study, telephone follow-up